CARACTERIZAÇÃO DOS LATOSSOLOS DA CHAPADA DE ARAGUARI: MINERAIS ARGILOSOS, GRANULOMETRIA E EVOLUÇÃO - Oliveira, Luiz Antônio de (Caminhos de Geografia, 2003)
The mineralogical composition of the latosols in the study area as determined by X-ray diffraction. Kaolinite and goethite is the dominant mineral in all profile (dark red, red-yellow and lateritic soils). Gibbsite is a common mineral present in the upper part of the profile (dark red and redyellow soils), while in the lateritic soil occur only in the "matrizâ€? fraction. Hematite happens in the topsoils (dark red and red-yellow soils). Quartz dominates the coarse fraction in all materials and shows a higher variability in sizes, although it is predominantly fine sand-size. Anatase were also detected in the topsoil. The mineralogical composition of the materials indicates a high degree of weathering of the parent material, wich caracteristic for oxisols in the humid tropics.